2017
DOI: 10.3390/w9010017
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Modeling of the Upper Indus Basin: A Case Study from a High-Altitude Glacierized Catchment Hunza

Abstract: Abstract:The Soil and Water Assessment Tool (SWAT) model combined with a temperature index and elevation band algorithm was applied to the Hunza watershed, where snow and glacier-melt are the major contributor to river flow. This study's uniqueness is its use of a snow melt algorithm (temperature index with elevation bands) combined with the SWAT, applied to evaluate the performance of the SWAT model in the highly snow and glacier covered watershed of the Upper Indus Basin in response to climate change on futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 41 publications
(66 reference statements)
4
63
0
Order By: Relevance
“…SWAT was used by Abbaspour et al [18] to study climate change impact on Iran's water resources. Garee et al [19] studied climate change impact on the streamflows of Hunza watershed in Pakistan. According to their study, the overall temperature is anticipated to rise form 1.39 • C to 6.58 • C with 31% increase in precipitation causing 5-10% increase in streamflows by the end of the century.…”
Section: Introductionmentioning
confidence: 99%
“…SWAT was used by Abbaspour et al [18] to study climate change impact on Iran's water resources. Garee et al [19] studied climate change impact on the streamflows of Hunza watershed in Pakistan. According to their study, the overall temperature is anticipated to rise form 1.39 • C to 6.58 • C with 31% increase in precipitation causing 5-10% increase in streamflows by the end of the century.…”
Section: Introductionmentioning
confidence: 99%
“…This also applies to the UIB where only the lower-altitude area may have higher ET contributions, while the high elevation sub-catchments may have only minor annual ET due to their low average temperatures. For example, in Hunza basin of the UIB, Garee et al [97], reported a model ET equal to 18% of the precipitation, and indicating even lower ET in the higher altitude catchments. Therefore, in UIB, which is also a a high mountainous basin and have a mean annual water discharge of around 462 mm/y, the ET in UIB should not amount to such high values, almost equal to the observed runoff.…”
Section:  Evapotranspiration (Et) Estimatesmentioning
confidence: 99%
“…To solve this issues, ET products with relatively lower values were evaluated. one such ET data is the Esri_hydro "Average Annual Evapotranspiration" [98], which is based on the MOD16 Global Evapotranspiration Product, and derived from MODIS-satellite imagery by a team of researchers at the University of Montana, have comparatively lower ET-estimates, which match better the recommended values of Bookhagen and Burbank [96] or the ET-values reported by Garee et al, [97]. The MOD16-ET-data have a good resolution of 1 km 2 and are available over the period 2000-2011.…”
Section:  Evapotranspiration (Et) Estimatesmentioning
confidence: 99%
“…Another source of uncertainty is model structural uncertainty. Over the past few decades, several models with different structures have been applied in the UIB, including Hydrologiska Byråns Vattenbalansavdelning (HBV) (Akhtar et al, ), the Snowmelt‐Runoff Model (Tahir et al, ), the Soil and Water Assessment Tool (Garee et al, ), and the University of British Columbia watershed model (Ali et al, ; Hasson, ; Naeem et al, ). Other UIB studies have utilised fully distributed models, such as the Spatial Processes in Hydrology model (Lutz et al, ), the Water and Energy Budget‐based Distributed Hydrological Model (Shrestha et al, ), and TOPKAPI (Ragettli et al, ; Pellicciotti et al, ).…”
Section: Introductionmentioning
confidence: 99%